Evaluation of Antimicrobial Properties of Passiflora foetida Root Extract Sourced from Rehabilitated Coal Mining Sites in East Kalimantan - Utami, Indah Woro; Sapri, Sapri; Meray, Nishia Waya; As'ari, As'ari (Sciences of Pharmacy, 2025)
Utilizing cover crops like Passiflora foetida L. (rambusa) can mitigate significant environmental issues in post-coal mining terrain rehabilitation. Plants thriving in extreme environments are known for producing high levels of secondary metabolites with significant biochemical activity. This study sought to assess the antifungal and antibacterial effects of P. foetida root extracts derived from rehabilitated coal mine soil in East Kalimantan. The roots were macerated with solvents of differing polarity (ethanol, ethyl acetate, and n-hexane) for extracting specific fractions. Utilizing the Kirby-Bauer disc diffusion method, the antifungal efficacy was assessed against Candida albicans, Candida tropicalis, and Candida lipolytica at a 60% concentration. Conversely, the antibacterial efficacy was assessed against Shigella dysenteriae, Streptococcus mutans, and Cutibacterium acnes at a 10% concentration. The findings revealed that the fraction consisting of ethyl acetate demonstrated the most potent and extensive antibacterial efficacy. The ethanol extract and ethyl acetate fraction exhibited significant antifungal activity, particularly against C. tropicalis, with inhibitory zones that were similar to those of the positive control, fluconazole. The treatments exhibited significant differences, as confirmed by statistical analysis (ANOVA and Tukey's HSD test). Studies indicate that that P. foetida roots, particularly those from harsh settings, are a significant source of antimicrobial chemicals, with the semi-polar ethyl acetate fraction being the most promising for further development as a natural antibacterial and antifungal agent.